361 BENIGN AND MALIGNANT PROCESSES OF THE HUMAN LARYNX AS STUDIED BY OPTICAL COHERENCE TOMOGRAPHY. (1st January 2005) - Mahmood, U.; Ridgway, J.; Jackson, R.; Guo, S.; Su, J.; Armstrong, W.; Crumley, R.; Shibuya, T.; Chen, Z.; Wong, B.
Abstract : Purpose: Laryngeal pathology occurs in numerous forms, many of which cannot be reliably differentiated with clinical examination alone. As such, proper diagnosis often necessitates biopsy, which is not only technically challenging but also increases patient morbidity, such as by putting the patient at risk for dysphonia when involving the vocal cord. One emerging technology which may prove helpful in the diagnosis of laryngeal pathology is Optical Coherence Tomography (OCT). OCT uses the reflection of light waves to create real-time, non-invasive images of tissues at high resolution. The purpose of this study is to determine OCT's ability to differentiate normal from benign and malignant processes in the human larynx. Methods: Our laboratory assembled an OCT system which was adapted to function in the operating room. This system was used during cases that involved direct laryngoscopy to study various anatomical regions of the human upper aero-digestive tract of 40 adult patients. OCT was used to image healthy tissues and tissues displaying benign and malignant processes (as determined by biopsy). Benign laryngeal pathologies imaged included cysts, polyps, nodules, papilloma, fibrosis, follicular hyperplasia, granulation tissue, and tissue post-XRT, whereas malignant processes imaged included squamous cell carcinoma, adenocarcinoma, and neuroendocrine tumors. Results: OCT images of normal larynx displayed regions of various tissue density in accordance with expected boundaries between the epithelium, lamina propria, and various tissue structures such as glands and blood vessels. Moreover, OCT detected changes in tissue architecture which were characteristic for the various benign and malignant processes imaged. Conclusions: Given OCT's remarkable, non-invasive tissue imaging capabilities, it is hoped that this technology may one day serve to aid in the diagnosis of laryngeal disease, thereby reducing the morbidity from and dependence on biopsy.